Outpatient utilization of psychopharmaceuticals : comparison between Croatia and Scandinavian countries (2001–2003) - Štimac Grbić, Danijela (Array, 2009)
Abstract: The aim was to estimate outpatient consumption of psychotropic drugs in Croatia in correlation with Scandinavian countries. Data on drug utilization, from Zagreb Municipal Pharmacy, were used to calculate the number of defined daily doses (DDD) and DDD per 1000 inhabitants per day (DDD/TID) using Anatomical-Therapeutic-Chemical methodology(ATC) by WHO. Data of the Nordic Medico-Statistical Committee were used for Scandinavian countries. In Zagreb, total utilization of psychopharmaceuticals of 144.9 DDD/TID in 2001, 148.9 DDD/TID in 2002 and 141.9 DDD/TID in 2003. The anxiolytic/antidepressant ratio decreased in Zagreb by 35.19% (7.19 in 2001 and 4.66 in 2003), whereas in Scandinavian countries it showed a constant rate (0.7 in Finland, 0.4 in Denmark and Norway, and 0.3 in Sweden). The three-year utilization patterns show that Croatia has been ever more closely following Scandinavian countries although there have been a notable differences between Croatia and Scandinavian countries